Effectiveness of Internal Audit in Public Sector Organizations: a Case of Chirumhanzu Rural District Council - Ingwani, Isabel T (Midlands State University, 2017)
It is imperative that any internal audit department be effective especially in public sector organisations in order to improve service delivery to local citizens. This research focused on investigating the effectiveness of internal audit particularly Chirumhanzu Rural District Council. The research objectives are to investigate the effectiveness and independence of internal audit reporting structures, to determine audit types which can be utilised in promoting effectiveness, to assess the challenges faced by internal audit in promoting effectiveness, to examine the benefits of internal audit effectiveness and to recommend possible solutions or suggestions which can be adopted to promote internal audit effectiveness at Chirumhanzu Rural District Council. One of the key issues hindering internal audit effectiveness that have been looked at are the different reporting structures for internal audit and their impact on effectiveness and independence of internal audit. This key issue and other impeding factors have been investigated on and information sought in a bid to suggest possible solutions and recommendations in order to enhance internal audit effectiveness.